2017
DOI: 10.1002/jbmr.3177
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Surgery Versus Observation: Skeletal 5-Year Outcomes in a Randomized Trial of Patients With Primary HPT (the SIPH Study)

Abstract: Mild primary hyperparathyroidism (PHPT) is known to affect the skeleton, even though patients usually are asymptomatic. Treatment strategies have been widely discussed. However, long-term randomized studies comparing parathyroidectomy to observation are lacking. The objective was to study the effect of parathyroidectomy (PTX) compared with observation (OBS) on bone mineral density (BMD) in g/cm and T-scores and on biochemical markers of bone turnover (P1NP and CTX-1) in a prospective randomized controlled stud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
55
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 40 publications
4
55
0
1
Order By: Relevance
“…Multiple studies have reported increases in BMD after PTX, but only 3 have categorized results by gender while focusing on bone disease Of these three, Sharma et al and Ballem et al found a greater post‐PTX improvement in BMD in men than in women, while Dy et al determined that the extent of bone recovery after PTX was not affected by gender or menopausal status. The use of bisphosphonate, longer time for postoperative DXA scan (within 3 years of surgical intervention), and exclusive analysis at the most affected anatomical site were unique characteristics to the study by Dy et al that differed from our study which might explain the different results.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Multiple studies have reported increases in BMD after PTX, but only 3 have categorized results by gender while focusing on bone disease Of these three, Sharma et al and Ballem et al found a greater post‐PTX improvement in BMD in men than in women, while Dy et al determined that the extent of bone recovery after PTX was not affected by gender or menopausal status. The use of bisphosphonate, longer time for postoperative DXA scan (within 3 years of surgical intervention), and exclusive analysis at the most affected anatomical site were unique characteristics to the study by Dy et al that differed from our study which might explain the different results.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple studies have found that surgical intervention for sporadic PHPT (sPHPT) is associated with an increase in postoperative BMD, but only a few studies have examined gender differences in BMD improvement after PTX . In this retrospective study, we aimed to determine differences in laboratory data and BMD changes after PTX between men and women (both premenopausal [pre‐MP] and postmenopausal [post‐MP]) with sPHPT.…”
Section: Introductionmentioning
confidence: 99%
“…We initially identified 2219 potentially relevant articles, of which 51 were retrieved for detailed evaluation. Two RCTs from the same team or institution were included as they reported different outcomes [20,30]. One study not reporting essential information of outcomes was excluded [31].…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…One study not reporting essential information of outcomes was excluded [31]. Finally, 5 RCTs with 584 patients [20,30,[32][33][34] and 10 CSs with 12202 patients [19,21,[35][36][37][38][39][40][41][42][43] were included (▶Fig. 1).…”
Section: Study Selection and Characteristicsmentioning
confidence: 99%
“…Bone health is a clinical concern in PHPT patients, especially in those treated conservatively. Recent studies found a significant BMD decrease in patients treated conservatively and a significant positive BMD increase in patients who underwent PTX (6,7). High-resolution peripheral quantitative computed tomography (HRpQCT) analysis has shown improvement in bone microarchitecture, cortical thickness, density, and estimated strength following PTX in female PHPT patients (8).…”
Section: Introductionmentioning
confidence: 99%